"Overdose of a Face": The Power of a Portrait of Ingrid Bergman and its Conse- quences - Vidal, Clara (Madrygal. Revista de Estudios Gallegos, 2018)
This work deals with the reading of a poem by Manuel Álvarez Torneiro taking into account the power of the image and the physical and psychic consequences that can come to awaken in the recipients of the work of art. In the analysis of the poem, we keep in mind both the resources: resources used in the verses and the situation that can be imagined that the ‘poetic self’ is going to go through, because this is still an example of an artistic admirer who allows himself to be moved by the image he sees, in the same way that the reader of the poem could be too. In this sense, it is the artistic representation in general that moves the viewer, the creation of life that is made thanks to the shock he suffers and the consequences that come from that shock; always, all these aspects, taking as reference the example of the poem object of study, “Tardes de Ingrid Bergman”, an excuse used to treat these subjects that can be applied to any possible artistic commotion.
Keywords: Stendhal Syndrome; Agalmatophilia; Galician Literature; Galician Poetry; Manuel Álvarez Torneiro; Poem “Tardes de Ingrid Bergman”.